The Influence of Cooperative Group Investigation on Students Learning Result in Natural Science Subject for Grade VIII in Kota Komba East Manggarai - Demezt, Yosef Frina; Masitoh, Siti; Mariono, Andi (Universitas Malikussaleh, 2019)
The study aims to find out the influence of Cooperative Group Investigation on the student's learning result in Natural Science Subject for Grade VIII in Kota Komba East Manggarai. It is a quantitative research, using a quasi-experiment method. The variables are: (1) The Independent Variable that is the learning design model named Cooperative Group Investigation; and (2) The Dependent Variable consist of the learning activity and the result of the learning. The technique of data collection exerts the achievement test. The sample of the research applies to 88 students in Grade VIII of Junior High School (SMP) during the 2018-2019 academic years in Kota Komba East of Manggarai. This research is carried out in four groups, namely: (1) Grade VIII of SMP Satu Atap Pedak, is as a control group; (2) Grade VIII of SMPN 8 is as a control group; (3) Grade VIII of SMP Pancasila Mukun, is as an experimental group; (4) Grade VIII of SMPN 3 is as an experimental group. Hypothesis testing is using analysis of variance (ANOVA) with the aid of SPSS 22. The result of the analysis concludes that the Cooperative Group Investigation gives a significant influence on student's learning, as it represents in the value of F 19,696 > 0,000 with the degree of sig on 0.05 (5%).